Faktor-Faktor yang Memengaruhi Minat Nasabah Menggunakan Aplikasi BMT NU-QIMAH Dengan Model Technology Acceptance Model (TAM): Factors Influencing Customer Interest in Using the BMT NU-QIMAH Application Using the Technology Acceptance Model (TAM) - Isnani, Wakik; Alaika, Rochmatullah (IJABAH: Indonesian Journal of Sharia Economics, Business, and Halal Studies, 2024)
This research was conducted with the aim of finding out what factors can influence customer interest in using the BMT NU-Q application, so this research tries to identify using a technology acceptance model, namely the Technology Acceptance Model by selecting the variables ease of use, usefulness, security and promotion in influencing customer interest in using the BMT NU-Q application. This study uses a quantitative approach. The population in this research is the BMT NU Cermee Branch customers who use the BMT NU-Q application, namely 184 customers, while the sample was determined at 114 respondents. The data source in this research is primary data. The data analysis method used is multiple linear regression analysis. The results of this research indicate that partially ease of use does not have a significant effect on customer interest in using the BMT NU-Q application. Usefulness has a significant effect on customer interest in using the BMT NU-Q application. Security also has a significant effect on customer interest in using the BMT NU-Q application. And promotions also have a significant effect on customer interest in using the BMT NU-Q application. Meanwhile, simultaneously ease of use, usefulness, security and promotion have a significant effect on customer interest in using the BMT NU-Q application.